2004
DOI: 10.1051/gse:2003053
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the frequency of Asian cytochrome B haplotypes in standard European and local Spanish pig breeds

Abstract: -Mitochondrial DNA has been widely used to perform phylogenetic studies in different animal species. In pigs, genetic variability at the cytochrome B gene and the D-loop region has been used as a tool to dissect the genetic relationships between different breeds and populations. In this work, we analysed four SNP at the cytochrome B gene to infer the Asian (A1 and A2 haplotypes) or European (E1 and E2 haplotypes) origins of several European standard and local pig breeds. We found a mixture of Asian and Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 4 publications
1
19
0
4
Order By: Relevance
“…Other studies confirmed some introgression events of Asian pig breeds in most European commercial breeds and evidence that local Spanish breeds have never been introgressed with Asian neither with European commercial populations [47][49]. In this sense, studying miRNAs differentially expressed between European and Asian pig breeds could contribute to understand their phenotypical differences.…”
Section: Introductionmentioning
confidence: 66%
“…Other studies confirmed some introgression events of Asian pig breeds in most European commercial breeds and evidence that local Spanish breeds have never been introgressed with Asian neither with European commercial populations [47][49]. In this sense, studying miRNAs differentially expressed between European and Asian pig breeds could contribute to understand their phenotypical differences.…”
Section: Introductionmentioning
confidence: 66%
“…Comparison of Cytb and CR as phylogenetic markers to investigate genetic relationships of pig breeds Both the mtDNA Cytb and CR DNA sequences are widely used as phylogenetic markers in molecular systematics (Ghivizzani et al, 1993;Alves et al, 2003;Clop et al, 2004;Fang and Andersson, 2006;Wu et al, 2007;Jiang et al, 2008). However, compared with Cytb, CR has a larger sequence variation, and is useful to compare the genetic diversity in the study.…”
Section: Influence Of the Pig Breeds From Shandong By Modern Commercimentioning
confidence: 99%
“…According to their polymorphisms all pigs were classified into the Asian (A1 = CATA and A2 = CATG) or European (E1 = TGCG and E2 = TGTG) origins (Giuffra et al, 2000;Clop et al, 2004) in maternal lineage. In the European domestic pig breeds, not only European but Asian origin haplotypes as well exist, because of the gene introgression from Asian breeds into European population as mentioned above; whereas in Asian domestic pig breeds only Asian origin haplotypes existed.…”
Section: Influence Of the Pig Breeds From Shandong By Modern Commercimentioning
confidence: 99%
“…It is also one of the few European pig breeds that has remained genetically unaffected by the introgression of Chinese domestic breeds, which have altered to a varying degree (15-56%) the genetic -and consequently phenotypic, behavioural and reproductivecharacteristics of the most commonly exploited breeds of Europe (Alves et al, 2003;Clop et al, 2004). European pig breeds are often divided into two main types, the Celtic, with a general central and northern European origin assumed, and the Iberian or Mediterranean (e.g., Porter, 1993, pp.…”
Section: The Iberian Pigmentioning
confidence: 99%